The economics of workaholism: we should not have worked on this paper - Daniel S. Hamermesh; Joel Slemrod (Institute for the Study of Labor (IZA), 2005)
A large literature examines the addictive properties of such behaviors as smoking, drinking alcohol and eating. We argue that for some people addictive behavior may apply to a much more central aspect of economic life: working. Workaholism is subject to the same concerns about the individual as other addictions, is more likely to be a problem of higher-income individuals, and can, under conditions of jointness in the workplace or the household, generate negative spillovers onto individuals around the workaholic. Using the Retirement History Survey and the Panel Study of Income Dynamics, we find evidence that is consistent with the idea that high-income, highly educated people suffer from workaholism with regard to retiring, in that they are more likely to postpone earlier plans for retirement. The theory and evidence suggest that optimal policy involves a more progressive tax system than in the absence of workaholism.
Keywords: J26; H21; 330; addiction; retirement; labor supply; tax policy; Sucht; Leistungsmotivation; Theorie